2017
DOI: 10.1007/s10561-017-9624-7
|View full text |Cite
|
Sign up to set email alerts
|

Considering 3D topography of endothelial folds to improve cell count of organ cultured corneas

Abstract: The posterior side of the cornea is covered by the endothelial monolayer, which governs corneal transparency but cannot proliferate. Determination of endothelial cell density (ECD) is therefore the minimal and mandatory quality control in all eye banks. It avoids primary graft failures caused by endothelial insufficiency, and allows allocation of corneas to surgical techniques requiring different numbers of endothelial cells (ECs). Corneas stored in organ culture (17% of grafts worldwide), are characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…; Jumelle et al. ). As we have used research corneas, our study may have shown wrongly high values in the automatic CBLM.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Jumelle et al. ). As we have used research corneas, our study may have shown wrongly high values in the automatic CBLM.…”
Section: Discussionmentioning
confidence: 98%
“…Addressing this, Jumelle et al. () implemented a 3D EC counting method to increase cell sampling and to correct overestimation by the conventional en face counting performed in eye banks. In addition, regularly training the skills of the staff and optimizing the quality of the images is the key to reliable data (Lass et al.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the ECD, cells were counted on each field, and the mean of the five was calculated. We used the ImageJ freeware ( (accessed on 1 November 2016)) with a customized plugin ECD3D [ 16 ]. The observer chose areas where EC were most clearly visible and avoided folds when present.…”
Section: Methodsmentioning
confidence: 99%
“…An accurate monitoring of endothelial cell density was possible at day (D) 2, 26, and 28. n = number of cells counted; ECD endothelial cell density in cells/mm 2 . At D2, ( A ) raw image with endothelial cells, ( B ) each center was pointed according to the center method, ( C ) cells borders and each center were marked thanks to ImageJ plugin ECD3D [ 16 ]. At D26, ( D ) comparative raw image showed larger cells, ( E ) ECD count was determined with the same method, ( F ) reconstruction allowed global view of the studied sample.…”
Section: Figurementioning
confidence: 99%